Diversidade funcional das assembleias de peixes em múltiplos habitats de um estuário tropical - Maciel, Emanuelle Bezerra (2022)
The study of functional diversity is important to indicate aspects related to the role of biodiversity in ecosystem functioning and reveal changes occurring in the community, in face of increasing threats to global biodiversity and the need for species protection and conservation efforts. The objective of this work is to analyze the functional diversity of fish assemblages in multiple habitats of a tropical estuary. Six samplings were carried out in Mamanguape River estuary (Paraíba, Northeastern Brazil) between June 2015 and January 2016. Five habitats were selected according to the distinct characteristics of each environment and the salinity gradient, represented by sandy beach (SB), mudflat (MU), seagrass (SE), mangrove fringe (MF) and riparian vegetation (RV). In each habitat, three points were established and for each point three hauls. Fish were captured using a beach seine. In each haul, the environmental variables of salinity, transparency, depth, temperature, pH, water for chlorophyll a and sediment (fine sand and coarse sand) samples were also collected. For functional approach, 7 functional traits related to vertical habitat, feeding and locomotion (morphology) and trophic guild (diet) were used. The functional indices of functional richness (FRic), functional evenness (FEve), functional divergence (FDiv) and functional redundancy (FRed) and the Community-Weighted Mean (CWM) were calculated. The RLQ analysis combined with the fourth-corner method were performed in order to evaluate the relationships between the functional traits of the species and the environmental variables in the habitats. In the multiple estuarine habitats, a total of 27,036 fish belonging to 119 species were collected. The highest individual abundance and species richness were recorded in MU and SE, followed by MF, SB and RV. Significant differences were recorded between habitats only for FRic and FEve, with highest values of FRic in MU and SE, FEve in BE, BFM and RV, FDiv in BE and SE and FRed in BE, MU and SE. In general, functional diversity in the multiple habitats showed a pattern of low FRic, intermediate FEve and FRed, and high FDiv. The main functional traits predominant by CWM were the same in all habitats, being related to the zoobenthivorous guild, compressiform body, pectoral fin size, forked caudal fin, mouth opening size and caudal peduncle compression index, except for the zooplanktivorous guild that only dominated in SB, MU and SE. The RLQ highlighted two distinct groups based on the spatial separation: the first group was formed by unstructured habitats (SB and MU) with water column species (pelagic), zooplanktivorous habit, compressiform body, forked fin and index of compression of the caudal peduncle indicating the importance of of a type of feeding and swimming in these shallow and open environments, mainly associated with salinity, temperature and transparency; the second group was composed of the structured habitats (SE, MF and RV) with more bottom species (benthic and demersal), with different feeding habits (zoobenthivorous, insectivorous and piscivorous), and body shapes to explore more structured environments, being related to other environmental variables, such as fine sand. The fourth-corner showed some significant correlations specific to each habitat. In this study, the functional diversity of the ichthyofauna influences the multiple habitats associated with estuarine gradient. The habitats characteristics are essential to guarantee potential nursery areas, estuarine diversity and ecological integrity, contributing to the identification, management and conservation of estuarine environments.